(untitled) (Research, Society and Development, 2020)
Color is the observer’s first contact with the surface of objects and most people with the world. As natural to human experience, there is a tendency to prefer certain objects, elements, or artifacts over others; Knowing the means of manipulating these color preferences is therefore important to ensure effectiveness and acceptance in product development. The present work aimed to map and describe the color preferences through the groups of the color hue of the inhabitants of Caico, in the state of Rio Grande do Norte, Brazil, when they are related to fashion products. Being classified as a field research - survey, exploratory-descriptive objective, and quantitative-qualitative approach. The questionnaire was conducted during the VI EXPOTEC of IFRN/Caico with a sample of 170 individuals, comprising 117 females and 53 males, with ages ranging from 7 to 64 years. As a result, there was a predominant targeting of pink and violet hues, in general, and specifically in 3 of the 5 areas of the city, as well as a great refusal to the greenish hues identified in all regions of the city.